The Islamic worldview of God, man and nature, and their relationships - Sulaiman, Kabuye Uthman (Scholars Academic and Scientific Publisher -India, 2020)
The thrust of this study is: first, to describe the Islamic worldview of God, Man and the world, and their relationships. Its objectives are twofold: first, to delineate God-mankind relationship, God-world relationship, al-Dunya (this world)–al-Akhirah (the world hereafter) relationship, man-world relationship and man-man relationship or interpersonal relationship. Understanding these relationships is part and parcel of the Islamic theory of knowledge exposition and the discourse of Islamic civilization. Second, to provide the correct answers to the following deep questions: what is Man‟s place in the universe? And, what are the things that set humans apart from other creatures on earth? Third, to expound the Qur‟anic view on the uniqueness of human beings. The study contends that: first, human beings are characterized by three things, namely body, spirit and intellect or cognitive ability. Their bodies and souls connect them to the physical and the metaphysical worlds respectively, while their intellect enables them to acquire knowledge, formulate ideas or think creatively, dominate nature (develop the earth), reason, reflect, ponder and contemplate, and distinguish right from wrong, moral from immoral behaviour or truth from falsehood; it prevents them from blind following of forefathers and lower desires, which is termed as jahiliyyah. Hence, they are required to work towards the development of these three aspects, namely body, soul and intellect. They are commanded to be grateful to Allah for endowing them with the intellect as it separates them from animals and they are forbidden from performing any act that could result into its impairment or destruction.